2022
DOI: 10.3390/toxins14080533
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Monoclonal Antibody against Deoxynivalenol and Development of Immunoassays

Abstract: Fusarium toxins are the largest group of mycotoxins, which contain more than 140 known secondary metabolites of fungi. Deoxynivalenol (DON) is one of the most important compounds of this class due to its high toxicity and its potential to harm mankind and animals and a widespread contaminant of agricultural commodities, such as wheat, corn, barley, oats, bread, and biscuits. Herein, a hybridoma cell 8G2 secreting mAb against DON was produced by fusing the splenocytes with a tumor cell line Sp2/0. The obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Xirui et al ( 2021) synthesized three gold nanobeads (GNBs) in sizes of 94, 129, and 237 nm for LFAs of FB 1 in maize samples, and GNBs showed the enhanced colorimetric signal intensity compared with 20-40 nm AuNPs (Figure 4A). Similarly, Mokhtar et al (2022) used AuNPs with a diameter of 20 nm and gold nanoflowers (AuNF) at 75 nm as detection probes in LFAs developed based on the DON monoclonal antibody, and the results showed that the visual detection limit of 6.67 μg/mL in test strips developed based on AuNF was three times higher than that of AuNPs. Silver nucleation is another common strategy used to enlarge the extinction coefficient of AuNPs by increasing their particle size (Yeh et al, 2009).…”
Section: Nanomaterial-based Signal Amplification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xirui et al ( 2021) synthesized three gold nanobeads (GNBs) in sizes of 94, 129, and 237 nm for LFAs of FB 1 in maize samples, and GNBs showed the enhanced colorimetric signal intensity compared with 20-40 nm AuNPs (Figure 4A). Similarly, Mokhtar et al (2022) used AuNPs with a diameter of 20 nm and gold nanoflowers (AuNF) at 75 nm as detection probes in LFAs developed based on the DON monoclonal antibody, and the results showed that the visual detection limit of 6.67 μg/mL in test strips developed based on AuNF was three times higher than that of AuNPs. Silver nucleation is another common strategy used to enlarge the extinction coefficient of AuNPs by increasing their particle size (Yeh et al, 2009).…”
Section: Nanomaterial-based Signal Amplification Methodsmentioning
confidence: 99%
“…They are used in various fields for labeling, delivery of biomolecules, and sensing (Sperling et al., 2008). Since their first reported application in LFAs (Shyu et al., 2002), AuNPs have become the most widely used nanomaterials in LFA‐based devices due to their ease of production, stability, and compatibility with different biomolecules and their versatility (Elsir et al., 2022; Xirui et al., 2021). When excited with specific wavelengths, the conduction electrons of the NPs’ surface oscillate collectively, resulting in strong absorption and scattering of light (Liz‐Marzan, 2004), referred to as localized surface plasmon resonance, and this property of AuNPs is mainly harnessed for the development of sensitive colorimetric LFAs.…”
Section: Signal Amplification Methodsmentioning
confidence: 99%
“…Moreover, ELISA is a feasible technique for low-level detection and quantification of mycotoxins. Indirect competitive ELISA and immunoassay methods based on colloidal gold nanoparticles and gold nanoknife have been successfully developed and can be used to detect DON in agricultural products . A portable and reusable evanescent wave optofluidic immunosensor has been used to measure DON in situ based on the principle of an indirect competitive immunoassay …”
Section: Mycotoxin Prevention and Control Strategiesmentioning
confidence: 99%
“…In recent years, immunological detection technology has been widely used for residue analysis of small-molecule pollutants such as mycotoxins, pesticides, antibiotics, etc. [ 19 ]. The core reagent and challenge for establishing immunological detection technology is the preparation of mAbs, and the basis of high-quality core mAb reagents is the preparation of high-quality artificial antigens.…”
Section: Introductionmentioning
confidence: 99%